Comparative study of the intervention of anti-riot groups for the restoration of rights - Cardona Quiceno, Carolina; Puerto Joya, Edith Johana; Beltrán Peñuela, Karen Margarita; Fajardo Pascagaza, Ernesto; Cervantes Estrada, Luis Carlos (DIXI, 2021)
Objective: This article results from the research carried out by the ecsan Research Group on the relationship between education and pedagogy. It aims to analyze the intervention of riot control groups from Colombia, Chile and Brazil in social protest from national and international regulations. It consists of a structure and comparative analysis that includes the internal normativity that regulate the procedure to be followed in crowd control, properly the phases before, during and after, without forgetting the State and police structure. Method: Qualitative research, consisting of interpretative analysis, supported in primary and secondary sources, and triangulation of information. Results: In comparing the intervention in social protest, international organizations refer to a constant use of force by anti-riot groups in the countries under study, which can be reflected in complaints and sanctions for the uniformed, the police and the State regarding the intervention procedures of the social protest and other procedural texts that lack channels of dialogue on the part of the anti-riot groups. Conclusions: An institutional proposal for the Policía Nacional de Colombia is suggested, in favor of an assertive and prior communication with those who exercise their right to protest.